Ready-to-eat mango and peanut bar as a value-added alternative for producers and market demand - Dominique Moreno-Ayala; María Dolores Muy-Rangel; José Basilio Heredia; Diego Alonso Gastelum-Chavira; Josefina León-Félix; Octavio Valdez Lafarga; José Benigno Valdez-Torres (Applied Food Research)
In the search for added value for mango and peanut production in the state of Sinaloa, México; as well as the fulfillment of market demand for nutritious, easy-to-handle, and sensorial attractive foods, a study was conducted to optimize the preparation of a mango bar with walnuts under different processing conditions and ingredient mixtures, using Ataulfo mango pulp as the base material. A three-component mixture design was applied: mango (74–88 %), peanut (7–20 %), and walnut (1–5 %), with extreme vertices and two process variables (temperature and time). An optimized mango bar with dehydrated fruit was made under conditions of 60 °C for 3 h and a mixture of 85.8, 8.7, 3.5, and 2 % mango, peanut, walnut, and almond, respectively. The mango bars showed good microbiological quality, aw values of <0.6, significant protein, dietary fiber, minerals, and carotenoid content of 19 µg/g. The dehydrated mango bar with dried fruits is a ready-to-eat and easy-to-handle food alternative.